AN ANALYSIS ON CLASSROOM INTERACTION USING IRF (INITIATION-RESPONSE-FOLLOW UP) IN TEACHING AND LEARNING PROCESS AT IX E GRADE SMP N 2 SERIRIT - ., Ni Luh Seri Maratni; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., Putu Eka Dambayana S., S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Tujuan dari penelitian ini adalah untuk mendeskripsikan 1) Tipe interaksi kelas apa yang digunakan oleh guru dan siswa selama proses belajar dan mengajar di SMP N 2 Seririt, 2) Apa fungsi dari masing-masing tipe interaksi kelas selama proses belajar dan mengajar dikelas. Subjek dari penelitian ini adalah guru dan kelas IX E SMP Negeri 2 Seririt. Penelitian ini menggunakan rancangan kualitatif dalam bentuk study kasus. Instrument yang digunakan dalam mengumpulkan data adalah peneliti, kamera, lembar observasi, panduan wawancara. Hasil dari analisi menunjukkan ada 9 tipe Sinclair dan Coulthard (1975) teori yang dikenal dengan IRF (Initiation-Response-Follow up) yang terjadi selama interaksi di kelas. Masing-masing tipe tersebut adalah: question, inform, invitation, direction, prompt, encouragement, ignoring, acknowledge and response. Tipe interaksi kelas yang paling sering terjadi adalah response dan yang paling sedikit adalah ignoring. Ada tigabelas fungsi yang berbeda di setiap tipe interaksi kelas yang ditemukan berdasarka Sinclair dan Coulthard (1975) di level act, diantaranya adalah starter, directive, informative, clue, reply, bid, react, nomination, accept, acknowledge and prompt. Kata Kunci : Kata kunci: Interaksi kelas, Sinclair dan Coulthard (1975) teori This study aimed at describing (1) what types of classroom interaction are used by English teacher and students during teaching and learning process in SMP N 2 Seririt, (2) What are the functions of each type of classroom interaction during teaching and learning process in SMP N 2 Seririt. The subjects of the study were the teacher and students in IX E class SMP Negeri 2 Seririt. This study was qualitative in the form of case study. The instruments used in collecting the data were: the researcher, video camera, observation sheet, and interview guide. The result of the analysis showed that there were nine types of Sinclair and Coulthard (1975) theory occurred during the interaction in the class which is known as IRF (initiation-response-follow up). Respectively the types were as follows: question, inform, invitation, direction, prompt, encouragement, ignoring, acknowledge and response. The response type was the most frequently occurred, while ignoring was the least frequently occurred during the teaching and learning process. There were thirteen different functions in each type of classroom interaction which was found based on Sinclair and Coulthard (1975) in the level of ac, they were: starter, directive, informative, clue, reply, bid, react, nomination, accept, acknowledge and prompt.keyword : Key words: Classroom interaction, Sinclair and Coulthard (1975) theory